A Note on the Immovable Point Theorem for Nonlinear Mappings - Sheth, Manas (Journal of Research in Vocational Education, 2024)
In this paper we discussed the generalization of the findings on fixed-point theorem in a complete convex metric space with uniformly normal structure of Mukherjee and Som as well as Gillespie and Williams.